2018
DOI: 10.1103/physrevd.98.064048
|View full text |Cite
|
Sign up to set email alerts
|

Weak field limit of infinite derivative gravity

Abstract: A form of infinite derivative gravity is free from ghost-like instabilities with improved small scale behavior. In this theory, we calculate the tree-level scattering amplitude and the corresponding weak field potential energy between two localized covariantly conserved spinning point-like sources that also have velocities and orbital motion. We show that the spin-spin and spin-orbit interactions take the same form as in Einstein's gravity at large separations, whereas at small separations, the results are dif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 40 publications
0
29
0
1
Order By: Relevance
“…[12,13] where it was shown that higher derivative gauge theories can be made ghost-free. In the gravitational context the same class of nonlocal actions were useful to obtain ghost-free nonsingular cosmological [14][15][16][17][18] and blackhole [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] solutions. Such nonlocal models were also applied in the framework of inflationary cosmology [34], and thermal field theory [35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…[12,13] where it was shown that higher derivative gauge theories can be made ghost-free. In the gravitational context the same class of nonlocal actions were useful to obtain ghost-free nonsingular cosmological [14][15][16][17][18] and blackhole [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] solutions. Such nonlocal models were also applied in the framework of inflationary cosmology [34], and thermal field theory [35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…From Eq. (32), it follows that if p 2 is a solution, then also its complex conjugate (p 2 ) * will be a solution.…”
Section: Pole Structurementioning
confidence: 99%
“…[20] for a more general treatment including some non-maximally symmetric spacetime. It was also noticed that the presence of nonlocality can regularize infinities and many efforts have been made towards the resolution of black hole [17,18,[21][22][23][24][25][26][27][28][29][30][31][32][33] and cosmological [16,[34][35][36][37] singularities. At the quantum level, the high energy behavior of loop integrals has been investigated in [38][39][40][41] and properties of causality and unitarity in [42,43] and [44][45][46][47], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] which demonstrated the possibility of constructing a quadratic curvature theory of gravity that is classically stable and unitary at the quantum level. It has also been noted that nonlocality can regularise infinities, and many efforts have been made to resolve black hole [13,14,[16][17][18][19][20][21][22][23][24][25][26][27]52] and cosmological [12,[28][29][30] singularities. Furthermore, renormalisability [31][32][33], causality [34,35], unitarity [36][37][38][39][40], scattering amplitudes [41][42][43], spontaneous breaking of symmetry [44,45] and counting of initial conditions [46,47] have also been discussed and analysed.…”
mentioning
confidence: 99%